Discussing the role of fiscal policy in a demand-led agent-based growth model - Esther Dweck; Matheus Vianna; Arthur Barbosa (EconomiA, 2020)
The global financial crisis led to a crisis in mainstream macroeconomic theory and to questioning the economic policies implemented before and after the crisis. One of the most relevant controversy concerns the role of fiscal policy. In order to present a different theoretical approach and discuss the role of fiscal policy, in this paper, we present an agent based micro-macro multisectoral model to analyze the fiscal policy in a complex evolutionary economy. We evaluate the impact of a set of different fiscal rules in terms of short run fluctuations and long-term growth. The main motivations are both to influence the public debate and to present an important theoretical tool. In terms of economic policy debate, in particular, we analyze the impact of the approval of a new fiscal rule that prevents any real growth of federal public expenditures for at least ten years in Brazil. Based on the simulation model, we compare 5 different combinations of fiscal policy on how they affect macro variables, such as GDP growth rate, GDP volatility and likelihood of crisis. We also test how each fiscal policy combination reacts to an external crisis. Results show that all scenarios that impose a tighter constraint to government spending present signs of self-defeating fiscal consolidation, including effect on firms' indebtedness. On the other hand, unconstrained countercyclical policy prevents contagious effect of external crisis, leading to a better economic performance and reducing the likelihood of crisis.
Keywords: 330; Agent-based models; Demand-led growth; Fiscal policy